2012
DOI: 10.1590/s0366-69132012000300008
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the green-like coloration and the structural and electronic properties of celadon glazes (I)

Abstract: Celadon glazes have been investigated by means of ordinary X-ray fluorescence analysis, and X-ray diffraction and X-ray absorption spectra using synchrotron radiation. The tentative glazes are prepared by mixing raw celadon materials of Masuda feldspar, limestone, quartz, and extra-added Fe2O3 of about 1wt% at thermal treatment till about 1300 °C. It is found that the glaze-colors strongly depend on the Fe2O3 amount and the high-temperature treatment under oxidizing and deoxidizing in the used kiln. Especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Thus, the smoothly small oscillating amplitude of the EXAFS spectra suggests that Fe ions are in glassy state of short-range order. We already confirmed that Seiji A, B, C, and D show the hallo-like X-ray diffraction pattern [6]. Thus, we are interested whether Fe ions in the celadon glaze are still in the micro-crystal state of Fe 2 O 3 or FeO structure or in non-crystal state to be perfectly complex free ions, because the EXAFS spectrum gives the structural information of the local circumstance around the X-ray absorbing ions in a material.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…Thus, the smoothly small oscillating amplitude of the EXAFS spectra suggests that Fe ions are in glassy state of short-range order. We already confirmed that Seiji A, B, C, and D show the hallo-like X-ray diffraction pattern [6]. Thus, we are interested whether Fe ions in the celadon glaze are still in the micro-crystal state of Fe 2 O 3 or FeO structure or in non-crystal state to be perfectly complex free ions, because the EXAFS spectrum gives the structural information of the local circumstance around the X-ray absorbing ions in a material.…”
Section: Resultsmentioning
confidence: 66%
“…The incident X-ray photons (I o ) were detected with an ionic chamber set before the specimens, which were already shown in Fig. 1 of our first paper [6], while the X-ray fluorescence photons (I) emitted from the surface of the specimens were simultaneously detected with an X-ray fluorescence detector. The flat surface of specimen was always set with about 45.0° to the incident X-ray beam.…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…Although Takada’s report constitutes a pioneering study that tried to scientifically elucidate the essence of akae , the effect of particle dispersibility of hematite and its microstructure on the color of akae remains insufficiently understood. Recently, although some detailed investigations have been done into akae of the old Imari and Chinese porcelain from the historical viewpoint by using a state-of-the-art analytical method, the essential coloring mechanism of akae is still not clear. ,, …”
Section: Introductionmentioning
confidence: 99%